2014
DOI: 10.1111/1440-1681.12244
|View full text |Cite
|
Sign up to set email alerts
|

α‐Lipoic acid prolongs survival and attenuates acute kidney injury in a rat model of sepsis

Abstract: Acute kidney injury is a frequent and serious complication in patients with severe sepsis. α-Lipoic acid (ALA), a naturally occurring dithiol compound, has been shown to possess anti-inflammatory and anti-oxidative properties. In the present study we investigated whether ALA could attenuate acute kidney injury and improve survival in a rat model of sepsis. Rats were subjected to caecal ligation and puncture (CLP) to induce sepsis. α-Lipoic acid (200 mg/kg) was administered by oral gavage either immediately (ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 58 publications
1
17
0
Order By: Relevance
“…A recent research from Wongmekiat et al (2013) has demonstrated that ALA mitigates renal injury in rats with obstructive nephropathy [18], suggesting a therapeutic role of ALA in renal diseases. Interestingly, our prior research has demonstrated that ALA can prolong survival and attenuate AKI in a rat model of sepsis, possibly by the anti-inflammatory actions [19]. Nonetheless, the underlying regulatory mechanisms remain unclear and require to be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…A recent research from Wongmekiat et al (2013) has demonstrated that ALA mitigates renal injury in rats with obstructive nephropathy [18], suggesting a therapeutic role of ALA in renal diseases. Interestingly, our prior research has demonstrated that ALA can prolong survival and attenuate AKI in a rat model of sepsis, possibly by the anti-inflammatory actions [19]. Nonetheless, the underlying regulatory mechanisms remain unclear and require to be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…Rats are commonly used in animal experiments of distant organ injury caused by inflammation as they have structural and functional similarities to humans . In this study, rats were chosen to investigate the effect of ALA on AP‐induced cardiac injury.…”
mentioning
confidence: 99%
“…Because ROS production is a major causative factor of renal dysfunction in cisplatin-induced renal dysfunction, 35 we selected LA as the drug to attenuate the renal dysfunction. [25][26][27][28] As shown in Fig. 7B, the effect of the hydro-gel/LA scaffold on cell viability was similar to that of the hydrogel without LA.…”
Section: Resultsmentioning
confidence: 76%
“…1). [25][26][27][28] Experimental section Materials Collagen (type I, M w = 250 kDa) was purchased from Bioland (Cheonan, Korea). The γ-PGA (K + form, M w = 500 kDa) was from BioLeaders Corporation (Daejeon, Korea).…”
Section: Introductionmentioning
confidence: 99%